2022
DOI: 10.1021/jacs.1c10173
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modulation of Amyloid-β (1–42) Aggregation and Toxicity by Structure-Based Rational Design

Abstract: Several point mutations can modulate protein structure and dynamics, leading to different natures. Especially in the case of amyloidogenic proteins closely related to neurodegenerative diseases, structural changes originating from point mutations can affect fibrillation kinetics. Herein, we rationally designed mutant candidates to inhibit the fibrillation process of amyloid-β with its point mutants through multistep in silico analyses. Our results showed that the designed mutants induced kinetic self-assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Since the self-assembly property of Aβ can be modulated by interrupting or enhancing the contact of the hydrophobic core domains, it would be possible to target the hydrophobic core regions in order to prevent or reduce the capacity of Aβ for self-assembling. Based on such findings, as well as in silico and in vitro analyses, we have previously shown that rationally designed point mutants of Aβ42 can suppress fibrillar aggregation . In particular, we identified two hydrophobic residues (Phe19 and Ile32) which are crucial for facilitating oligomerization of Aβ42 .…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Since the self-assembly property of Aβ can be modulated by interrupting or enhancing the contact of the hydrophobic core domains, it would be possible to target the hydrophobic core regions in order to prevent or reduce the capacity of Aβ for self-assembling. Based on such findings, as well as in silico and in vitro analyses, we have previously shown that rationally designed point mutants of Aβ42 can suppress fibrillar aggregation . In particular, we identified two hydrophobic residues (Phe19 and Ile32) which are crucial for facilitating oligomerization of Aβ42 .…”
Section: Introductionmentioning
confidence: 74%
“…Recent studies have attempted to rationally design candidate drugs in order to improve existing therapeutic approaches or suppress the fibrillar amyloid aggregation process altogether based on the accumulated knowledge of interlinked dynamics of IDPs, intermediate oligomers, and their pathogenesis to date. For example, a pharmacophore in MAP tau for the binding of small molecules was shown to enhance the binding of potential therapeutic agents . In addition, an epitope-specific method for antibody design has been reported, which allows development of antibodies to the desired binding epitopes of amyloidogenic IDPs .…”
Section: Introductionmentioning
confidence: 99%
“…In T2D, hIAPP is secreted from islet β-cells, and its aggregation has been linked to β-cell destruction. However, much therapeutic effort to target hIAPP aggregation failed to cure T2D. On the other hand, pramlintide, an FDA-approved drug for T2D, is a nonamyloidogenic hIAPP analogue. , Thus, we may speculate that nonamyloidogenic Aβ analogues may provide a new therapeutic approach toward AD treatments.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pramlintide, an FDA-approved drug for T2D, is a nonamyloidogenic hIAPP analogue. 81,82 Thus, we may speculate that nonamyloidogenic Aβ analogues 83 may provide a new therapeutic approach toward AD treatments.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…To initiate the aggregation process, it is necessary to create aggregation seeds first, which grow quickly after that. In experimental conditions, at the concentration of peptide in a µM range, the seeding of Aβ42 takes many hours [15,31]. By extrapolating to the interstitial concentration of beta-amyloid in vivo, which is in an nM range, the seeding would take several months [15].…”
Section: Formation Of Amyloid Depositsmentioning
confidence: 99%